2011
DOI: 10.1016/j.diff.2011.05.007
|View full text |Cite
|
Sign up to set email alerts
|

The functional role of reactive stroma in benign prostatic hyperplasia

Abstract: The human prostate gland is one of the only internal organs that continue to enlarge throughout adulthood. The specific mechanisms that regulate this growth, as well as the pathological changes leading to the phenotype observed in the disease benign prostatic hyperplasia (BPH), are essentially unknown. Recent studies and their associated findings have made clear that many complex alterations occur, involving persistent and chronic inflammation, circulating hormonal level deregulation, and aberrant wound repair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
104
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(110 citation statements)
references
References 146 publications
(170 reference statements)
3
104
0
Order By: Relevance
“…Moreover, a recent in vivo wound healing study linked mechanical forces to inflammatory activation of fibroblasts via focal adhesion kinase (FAK), a transducer of both inflammatory and physical signals: In a mouse model of hypertrophic scar formation, fibroblast-specific knockdown of FAK resulted in reduced inflammation and fibrosis, compared with control mice [50]. While not involving cancer, these studies indicate that changes in tissue architecture as a result of aberrant epithelial proliferation, an early neoplastic response, may result in activation of inflammatory signalling by stromal fibroblasts, a hypothesis supported by reports of inflammatory signalling by stromal fibroblasts in benign prostatic hyperplasia [50][51][52][53]. Taken together, it is reasonable to hypothesize that biomechanical forces applied by aberrant proliferation of transformed epithelial cells in incipient tumours may be one of the physiological signals that trigger pro-inflammatory signalling in resident tissue fibroblasts.…”
Section: Activation By Biomechanical Forcesmentioning
confidence: 73%
“…Moreover, a recent in vivo wound healing study linked mechanical forces to inflammatory activation of fibroblasts via focal adhesion kinase (FAK), a transducer of both inflammatory and physical signals: In a mouse model of hypertrophic scar formation, fibroblast-specific knockdown of FAK resulted in reduced inflammation and fibrosis, compared with control mice [50]. While not involving cancer, these studies indicate that changes in tissue architecture as a result of aberrant epithelial proliferation, an early neoplastic response, may result in activation of inflammatory signalling by stromal fibroblasts, a hypothesis supported by reports of inflammatory signalling by stromal fibroblasts in benign prostatic hyperplasia [50][51][52][53]. Taken together, it is reasonable to hypothesize that biomechanical forces applied by aberrant proliferation of transformed epithelial cells in incipient tumours may be one of the physiological signals that trigger pro-inflammatory signalling in resident tissue fibroblasts.…”
Section: Activation By Biomechanical Forcesmentioning
confidence: 73%
“…23 It should be noted that the association between prostate volume and hypertension resulted very close to the level of MetS significance (HR ¼ 1.962, 95% confidence interval: 0.996-3.864, P ¼ 0.055, see Figure 3), suggesting that this component may be a potential contributor for the growth of prostate volume, as reported by other Authors. 5,21,23 A wealth of recent epidemiological and histopatological studies have clearly indicated that prostate chronic inflammation is not only a common finding in BPH, 24,25 but also has a primary role in triggering prostatic cells overgrowth. 26,27 Potential causes for inflammation and immune dysregulation in the prostate include exposure to dietary factors, and metabolic variations.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic intraprostatic inflammation and subsequent chronic tissue remodeling are determinant factors in the development and progression of prostatic diseases, including BPH (see Kramer et al (2007), Fibbi et al (2010b) and Schauer & Rowley (2011) for reviews). A possible hormonal basis for prostate inflammation is suggested by preclinical studies in animal models, demonstrating that hypogonadism induced surgically (Robinette 1988, Desai et al 2004, Quintar et al 2006, Meng et al 2011 or by HFD administration ) exacerbate prostate inflammation and that exogenous testosterone can counteract this effect.…”
Section: Discussionmentioning
confidence: 99%
“…Although primarily characterized by hyperproliferation of both stromal and epithelial cells, a wealth of recent epidemiological and histopatological studies have clearly evidenced that chronic inflammation is a common finding in BPH (see Kramer et al (2007), Fibbi et al (2010b) and Schauer & Rowley (2011) for reviews). Data from two large-scale studies have indicated that chronic inflammatory infiltrates are associated with higher prostatic volume, a higher risk of BPH progression, and acute urinary retention , Nickel et al 2007.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation